The effects of financial health and company characteristics on Integrated Reporting - Nurkholis Nurkholis (University of Merdeka Malang, 2020)
Integrated Reporting up to now is still prepared voluntarily, so that there are still very few companies that implement it. Using secondary data obtained from published annual financial statements of 20 state owned enterprises (SOE’s) from 2012-2018 (140 pooled observations), this study aims to predict the effect of financial health indicators and company characteristics related to company’s size, age, and type of industry on the extent of Integrated Reporting disclosure of SOE’s listed in the Indonesia Stock Exchange (IDX). Through descriptive and inferential statistic performed, this study provides empirical evidence that indicators of financial health and the size of companies have negative effects on the extent of Integrated Reporting disclosure. Variables of age and type of industry do not affect the extent of Integrated Reporting disclosure. These results indicate that, in line with signaling theory, the lower the level of financial health and the smaller the size of the company, the more likely that the company will try to further increase the extent of disclosure in its Integrated Reporting. JEL Classification: G32, M41 DOI: https://doi.org/10.26905/jkdp.v24i4.4297